Prenatal diagnosis and molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome derived from chromosome 21q11.2-q21.1 and a literature review - Chih-Ping Chen; Ming Chen; Chia-Hsun Wu; Chen-Ju Lin; Schu-Rern Chern; Peih-Shan Wu; Yen-Ni Chen; Shin-Wen Chen; Shun-Ping Chang; Li-Feng Chen; Wayseen Wang (Elsevier, 2017)
Objective: We present prenatal diagnosis and molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome (sSMC) derived from chromosome 21q11.2-q21.1, and we review the literature of an sSMC(21) with a duplication of 21q11.2-q21.1. Case report: A 40-year-old woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 47,XX,+mar [18]/46,XX [4]. The parental karyotypes were normal. Prenatal ultrasound findings were unremarkable. aCGH analysis of cultured amniocytes revealed a 2.855-Mb duplication of 21q11.2-q21.1 encompassing the genes of LIPI, ABCC13 and NRIP1. Metaphase fluorescence in situ hybridization analysis on cultured amniocytes revealed a result of 47,XX,+mar .ish der(13/21) (D13/21Z1+) [10]. Spectral karyotyping analysis determined the origin of chromosome 21 in the sSMC. A female fetus was delivered with no phenotypic features of Down syndrome and no structural abnormalities. We discuss the genotype-phenotype correlation of LIPI, ABCC13 and NRIP1, and review the literature of an sSMC(21) associated with dup(21)(q11.2q21.1). Conclusion: aCGH is useful for identification of the nature and genetic component of a prenatally detected sSMC.